SELECTING OPTIMAL MODES OF KNOTWEED RAW MATERIALS PRESSING OUT AND DEVELOPING TECHNOLOGY FOR OBTAINING DRY EXTRACT - A.T. Takibayeva,; I.V. Kulakov,; D.M. Sydykova,; A.S. Kapbassova,; Zh.B. Rakhimberlinova, (Academic Scientific Journal of Chemistry, 2019)
A complex of studies on the choice of optimal conditions for extraction of medicinal plant raw materials of poultry mountain and the development of technology for obtaining dry extract from plant raw materials was concluded. There is a tendency to develop resource-saving technologies in ways of creating new drugs from plant raw materials. This is ensured by the use of various extractants, schemes and extraction modes, using equipment that can significantly increase the release of radioactive and active substances.Several variants of extraction of raw materials by the proposed technology using different temperature regimes and time exposures were studied. We used 40, 50, 60, 70% aqueous solutions of ethyl alcohol as an extractant and determined that 60% aqueous solution of ethyl alcohol has a better ability with respect to the amount of flavonoid grass red tape to select the optimal method of extraction of plant raw materials. Quantitative determination of the amount of flavonoids in the herbs of the red ribbon is made in four Parallels and their metrological characteristics are calculated.According to the experimental data, the optimal number of particles was 2 mm.